Education and Training Program towards Work Achievement for Employees of Developer’s Company - Yuliati, Dewi (TRIKONOMIKA, 2016)
The purpose of this research is to know the influence of education and training programs towards work’s achievement for employees in developer’s company Kota Bunga, Puncak, Cianjur Regency. Education and training programs consist of hardware and software dimension; as well as work achievement with the dimension of quantity and quality. Education and training variables were both assessed in terms of respondents’ responses. The results reflect that most employees would assume that training is a very important. Work achievement is the contribution of individuals or groups either in quantity or in quality against the purpose of the company. Based on the respondents’ responses, employees’ work achievement is considered as excellent. Hypothesis test shows that there is a significant and positive influence on the program of education and training towards work achievement of employees.